Computer-Aided Design (CAD) Training for Appropriate Technology (TTG) to Enhance the Competence of Vocational High School Students in East Java - Mulyadi; Edi Widodo; A'rasy Fahruddin; Akhmad Ahfas (Talenta Publisher, 2025)
This community service programme aimed to enhance the competencies of vocational high school students in East Java through Computer-Aided Design (CAD) training for Appropriate Technology (AT). Held on 13 June 2025 at the Mechanical Engineering Study Programme, Universitas Muhammadiyah Sidoarjo (Umsida), the activity was part of the Institutional Community Service Grant initiative. A total of 20 students from four partner schools participated, with each school sending five representatives. The training focused on developing students’ technical skills in designing AT products using CAD software and simulating basic fluid mechanics relevant to product development. Expert instructors, certified by the National Professional Certification Board (BNSP), delivered hands-on sessions to ensure strong practical learning outcomes. The results showed significant improvements in students’ technical abilities in CAD-based product design, a better understanding of engineering concepts, and greater readiness to apply these skills in industry-related contexts. This programme represents a strategic effort to bridge the gap between vocational school graduates’ competencies and industry demands, while also fostering innovation and the potential for technology-based entrepreneurship.